Use of a Free Vascularized Medial Femoral Condyle Flap for Revision Surgery in a Pediatric Patient with Congenital Pseudarthrosis of the Clavicle - Atsuro Murai; Kaoru Tada; Mika Nakada; Masashi Matsuta; Katsuhiro Hayashi; Hiroyuki Tsuchiya (Case Reports in Orthopedics)
The most common surgical treatment for congenital pseudarthrosis of the clavicle (CPC) is resection of the pseudarthrosis, placement of an autologous bone graft, and Kirschner wire or plate fixation. However, in some cases, bone fusion cannot be achieved at the first surgery, and an additional surgery is required. We present a case report of a boy with a right CPC who failed radiographic bone union after the first surgery. He subsequently underwent revision surgery with resection of the pseudarthrosis, plate fixation, and establishment of a vascularized medial femoral condyle (MFC) flap to ensure bone union. Three months after the revision surgery, a radiographic bone union was achieved, and no symptoms were observed for one year after the operation. There have been no previous reports of the use of a vascularized MFC flap as a treatment for CPC. We believe that this technique effectively ensures bone union during revision surgery for CPC.